Electrochemical and structural behavior of poly(3-methylthiophene) at different interfaces: Synthesis and characterization - Leandro Rodrigues Koenig; Mayara Masae Kubota; Henrique de Santana (Results in Chemistry)
Recent advances in poly(3-alkylthiophenes) (P3ATs) research have facilitated application of these materials in advanced organic devices in which charge transport and energy storage properties are required, owing to their ability to stabilize oxidized structures in their polymer chains. To improve understanding their associated behavior, systematic studies of poly(3-methylthiophene) (P3MT) electrochemically deposited on indium tin oxide (ITO) and platinum were carried out, using cyclic voltammetry, UV–Vis. absorption spectroscopy, ex situ and in situ Raman spectroscopy and Electrochemical Impedance Spectroscopy (EIS). The results showed that the electrochemical synthesis conditions and applied potential determine the stability of the radical cation and dication segments in the polymer matrix. With the knowledge acquired, the conditions for applying these results to the interface, involving P3MT and titanium dioxide (TiO2) impregnated with camphorsulfonic acid, could be defined. This system was characterized by ex situ Raman techniques and EIS. A significant increase in the formation of the radical cation segment was observed after electrochemical synthesis. Furthermore, it was found that the transition of the radical cation to dication segments occurs over time, favoring an improved stability between these segments at the interface with TiO2.